2004
DOI: 10.1104/pp.104.041293
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate Accumulation Inhibits Growth at Chilling Temperature in Arabidopsis

Abstract: The growth of Arabidopsis plants in chilling conditions could be related to their levels of salicylic acid (SA). Plants with the SA hydroxylase NahG transgene grew at similar rates to Col-0 wild types at 23°C, and growth of both genotypes was slowed by transfer to 5°C. However, at 5°C, NahG plants displayed relative growth rates about one-third greater than Col-0, so that by 2 months NahG plants were typically 2.7-fold larger. This resulted primarily from greater cell expansion in NahG rosette leaves. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
173
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(187 citation statements)
references
References 81 publications
7
173
2
4
Order By: Relevance
“…We found non-enzymatic conversion of IC to SA under physiological conditions to be negligible. Furthermore, total SA accumulates to levels similar to those induced by pathogen in Arabidopsis grown at 5°C (32), a temperature at which non-enzymatic conversion of IC to SA should be insignificant. In P. aeruginosa, a direct comparison of the enzymatic (k cat Pae PchB (50)) and non-enzymatic (64) rates of SA formation from IC indicates that the enzyme accelerates SA formation ϳ4 ϫ 10 5 -fold (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found non-enzymatic conversion of IC to SA under physiological conditions to be negligible. Furthermore, total SA accumulates to levels similar to those induced by pathogen in Arabidopsis grown at 5°C (32), a temperature at which non-enzymatic conversion of IC to SA should be insignificant. In P. aeruginosa, a direct comparison of the enzymatic (k cat Pae PchB (50)) and non-enzymatic (64) rates of SA formation from IC indicates that the enzyme accelerates SA formation ϳ4 ϫ 10 5 -fold (64).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, a more general role for SA as a mediator of diverse stress responses has been emerging. For example, in Arabidopsis SA is synthesized in response to abiotic stresses such as UV-C (30), ozone (31), cold (32), and heat (33,34) and has been shown to play a role in stress-induced developmental transitions, including flowering (35) and senescence (36). Although AtICS1 has been confirmed to be involved in many of these processes, it has only been implicated in others, such as cold-tolerant growth.…”
mentioning
confidence: 99%
“…S2). Similarly, when free SA levels were analyzed (Scott et al, 2004), the Col-0 plant roots colonized with FB17 showed increased free SA titers compared to plants without FB17 colonization (data not shown).…”
Section: Fb17 Root Colonization Triggers Isr and Protects Arabidopsismentioning
confidence: 99%
“…Although we cannot exclude potential effects of the catechol by-product of NahG-mediated SA degradation, the phenotypic effects seen in the NahG transgenic plants of increased rosette biomass through greater cell expansion and increased seed yields are known to be directly associated with reduced SA levels in Arabidopsis (39)(40)(41)(42). NahG-generated catechol may not accumulate to high levels (43), which in any case would cause growth inhibition (44) and not the growth enhancement observed.…”
Section: The F1 Hybrids Show Alterations To Hormone-regulated Genes Andmentioning
confidence: 99%